Evaluasi Implementasi Audit Energi dan Sistem Manajemen Energi ISO 50001:2018 di PT Putra Perkasa Abadi Site Borneo Indobara - Fidi Fitriadhi; Dwi Fitriadi; Desy Ardiyanti; Muhammad Osaegi Restu Amrulloh; Trio Aris C (BADAN PENERBIT STIEPARI PRESS, 2025)
Energy conservation is a strategic aspect in supporting operational efficiency and environmental sustainability in the mining sector. PT Putra Perkasa Abadi (PPA) Site Borneo Indobara is committed to implementing an energy management system based on ISO 50001:2018 as part of the national policy implementation, particularly referring to Government Regulation No. 33 of 2023 on Energy Conservation. This study aims to evaluate the implementation of internal energy audits and external ISO 50001:2018 audits conducted in 2024, focusing on strengthening the energy management system within coal mining operations. The research method employs a descriptive evaluative approach based on document analysis of internal and external energy audits. The evaluation is carried out using Energy Performance Indicators (EnPI), Energy Baseline (EnB), and the Cumulative Sum (CUSUM) method to assess energy performance trends. The results indicate that PT PPA has implemented a structured and integrated energy management system in accordance with ISO 50001:2018 standards and national energy conservation regulations. The implementation of energy audits supports the enhancement of energy management policies, including the identification of Significant Energy Use (SEU), monitoring of energy consumption, and the development of efficiency programs based on operational data. The external audit conducted by Sucofindo International Certification Services further validates the energy management system in place. This study highlights the importance of energy audits as an instrument to strengthen energy conservation implementation in the mining sector, aligning with government policies to promote energy efficiency and carbon emission reduction.